Successful retrieval of a fractured and embolised Judkin's catheter during a coronary angiogram. (4th July 2013) - Patra, Soumya; Sadananda, K S; Agrawal, Navin; Manjunath, Cholenahally Nanjappa
Abstract : We report the successful retrieval of a large broken segment of right Judkin's catheter using a snare catheter by a retrograde approach. A 69-year-old woman presented with an anterior wall myocardial infarction. A coronary angiogram revealed severe stenosis of distal left main coronary artery, ostio-proximal portion of the left anterior descending artery and the ostial left circumflex artery. During right shoot, the Judkin's right catheter was broken at almost 15  cm from the distal end. The distal end of the broken catheter was lying in the ascending aorta, whereas proximal end was in the left subclavian artery. First, we snared the distal end and pulled out the catheter in right common iliac artery but owing to the curvature of the fragment, this attempt was unsuccessful. Finally, we were successful in removing the fractured segment retrogradely through the arterial sheath placed in left femoral artery.